EFEKTIVITAS IKLAN CETAK HYDRO COCO DENGAN MENGGUNAKAN METODE DIRECT RATING METHOD (SURVEI PADA REMAJA DI GOR VELDROME RAWAMANGUN) - Jusuf Fadilah (Universitas Bina Sarana Informatika, 2017)
The competition of isotonic beverage products on the market today is getting tougher. Hydro Coco as an isotonic beverage that is currently very aggressive to carry out promotional and advertising activities. Hydro Coco which still holds the third position of top brand 2016 phase 1 isotonic beverage category, want to increase its position. There are still many people who are not interested in isotonic drink Hydro Coco because of the perception of society itself that still assume that by drinking coconut water, the body will become weak. For that, it needs a promotion strategy by emphasizing advertising as the main communication medium. The advertising creative message communication strategy has the purpose of informing about the advantages of Hydro Coco products as isotonic drinks derived from native coconut natural good for body.This research is about The Effectiveness of Hydro Coco Print Ads Using Direct Rating Method when viewed from the level of awareness, and the power of an advertisement to get the attention, understanding, arousing feeling, and the ability of the advertisement to influence consumer behavior. The results show that Hydro Coco print ads are quite successful in attention, readthougness, cognitive, affection, and behavior to buy Hydro Coco drinks.Keywords: Isotonic, Hydro Coco, Direct Rating Method